Impact of 48-h water and feed deprivation and hydroxychloride sources of copper and zinc on the metabolism and performance of grazing Nellore cattle during the dry period - Abreu, M. J.I. [UNESP]; Cidrini, I. A. [UNESP]; Ferreira, I. M. [UNESP]; Batista, L. H.C. [UNESP]; Bisio, G. H.M.; França, M. Q.S.; Reis, I. A. [UNESP]; Rodrigues, A. N. [UNESP]; Queiroz, A. C.M. [UNESP]; Neto, J. M.C. [UNESP]; Araújo, D. B.; Porcionato, M. A.F.; et al. (Elsevier, 2024)
Procedures such as transport and marketing can subject animals to water and feed deprivation and impair animal health and performance. Maintaining the mineral status of animals under these conditions can bring benefits to health and performance. The use of hydroxychloride mineral sources can improve mineral status, nutrient digestibility and performance. Two studies were conducted to investigate how the supplementation of 02 trace mineral sources of Cu and Zn and 48-hour water/feed deprivation would affect the performance and metabolism of grass-fed beef cattle. In the first study, 20 castrated and rumen-canulated Nellore steers (BW = 350 ± 132 kg; 20 m) were distributed in individual pens, in a 2 × 2 factorial arrangement: supplemental Cu and Zn sources from inorganic vs hydroxychloride (HTM) and 48-hours deprivation (WFD) vs unrestricted (WFU) access to water and feed. The 57d of study was divided into two periods: (1) Adaptation from -21d to -1d and (2) evaluation from 0d to 36d. Interaction between deprivation × period was detected (P < 0.05) for digestibility of DM (DMD), organic matter (OMD), neutral detergent fiber (NDFD), and acid detergent fiber (ADFD). Deprivation increased DMD, OMD, NDFD, and ADFD immediately after the deprivation period (3-5d), but impaired digestibility at longer periods such as 11-13d and 32-34d. DM (DMI) and nutrient intake (P = 0.075), as well as NDFD were higher in HTM. Several ruminal parameters were affected by deprivation: short-chain fatty acids concentration decreased, while rumen pH increased (deprivation × time; P < 0.05); decreased propionate, butyrate and increased isobutyrate, isovalerate, and valerate in WFD (deprivation × time; P < 0.05), respectively. In the second study, eighty-four intact Nellore males (BW = 260 ± 35 kg) were blocked by BW and randomly assigned to Urochloa brizantha cv. Marandu paddocks for 131d in a 2 × 2 factorial arrangement. Liver Cu was higher in WFU/HTM animals (mineral × deprivation; P < 0.05). Interaction between deprivation × period (P < 0.05) was detected for BW and average daily gain (ADG). On 2d and 12d after deprivation, WFD increased ADG and recovered the BW lost. In conclusion, water and feed deprivation imposed in these trials were able to impact several nutrient digestibility and ruminal fermentation parameters in short- and long-term. Performance was not affected by the studied factors. Furthermore, supplementation with sources of Cu and Zn hydroxychloride increased Cu in the liver and tended to increase DMI and NDFD.
Keywords: Beef cattle; Cattle on pasture; Fiber digestibility; Source of mineral; Water and feed deprivation